Determining phase transitions of layered oxides via electrochemical and crystallographic analysis. Issue 1 (31st January 2020) - Fröhlich, Katja; Abrahams, Isaac; Jahn, Marcus
ABSTRACT: The chemical diffusion coefficient in LiNi1/3 Mn1/3 Co1/3 O2 was determined via the galvanostatic intermittent titration technique in the voltage range 3 to 4.2 V. Calculated diffusion coefficients in these layered oxide cathodes during charging and discharging reach a minimum at the open-circuit voltage of 3.8 V and 3.7 V vs. Li/Li +, respectively. The observed minima of the chemical diffusion coefficients indicate a phase transition in this voltage range. The unit cell parameters of LiNi1/3 Mn1/3 Co1/3 O2 cathodes were determined at different lithiation states using ex situ crystallographic analysis. It was shown that the unit cell parameter variation correlates well with the observed values for chemical diffusion in NMC cathodes; with a notable change in absolute values in the same voltage range. We relate the observed variation in unit cell parameters to the nickel conversion into the trivalent state, which is Jahn-Teller active, and to the re-arrangement of lithium ions and vacancies. Graphical Abstract: uf0001